2017
DOI: 10.1021/acscatal.7b01719
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Promoted Selective Oxidation of Alcohols Using a Covalent Triazine Framework

Abstract: The formation of aldehydes and ketones via selective oxidation of alcohols is an essential transformation in organic synthesis. However, the usually harsh reaction conditions using toxic metal catalysts or corrosive reagents lead to undesired side products and wastes. Environmentally friendly and mild reaction conditions using metal-free catalysts remain a huge challenge. Herein, we report the use of a thiophene-based covalent triazine framework (CTF) as pure organic and visible-light-active photocatalyst for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
227
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 302 publications
(238 citation statements)
references
References 46 publications
8
227
0
3
Order By: Relevance
“…introduced a thiophene‐containing covalent triazine framework (CTF) located on mesoporous silica (SBS‐15) as a PC for the efficient and selective oxidation of alcohols to aldehydes and ketones with molecular oxygen as a green oxidant [Eq. (29)] . It is suggested that the uniform formation of CTF‐Th 99 inside the mesopores of SBA‐15 is due to the even distribution of carbon, nitrogen, and sulfur atoms in the material, which was confirmed by using elemental mapping.…”
Section: Sulfur‐containing Photosensitizersmentioning
confidence: 82%
“…introduced a thiophene‐containing covalent triazine framework (CTF) located on mesoporous silica (SBS‐15) as a PC for the efficient and selective oxidation of alcohols to aldehydes and ketones with molecular oxygen as a green oxidant [Eq. (29)] . It is suggested that the uniform formation of CTF‐Th 99 inside the mesopores of SBA‐15 is due to the even distribution of carbon, nitrogen, and sulfur atoms in the material, which was confirmed by using elemental mapping.…”
Section: Sulfur‐containing Photosensitizersmentioning
confidence: 82%
“…In particular, the semiconductor redox potentials of CPs can be precisely modified through electron‐donor or electron‐acceptor combinations, which in principle also create organic dyadic structure to facilitate charge separation. Recent research has demonstrated the use of CMPs in a variety of organic photoredox reactions . Cooper et al.…”
Section: Methodsmentioning
confidence: 99%
“…[139] This catalyst has alow-energy HOMO,w hich increases its oxidation nature.M esoporous silica was used as support as it dramatically increased conversions.T he authors attribute this to the increase in surface area for the supported variant. [139] This catalyst has alow-energy HOMO,w hich increases its oxidation nature.M esoporous silica was used as support as it dramatically increased conversions.T he authors attribute this to the increase in surface area for the supported variant.…”
Section: Angewandte Chemiementioning
confidence: 99%